Some correlates of teaching effectiveness among secondary school teachers in Ibadan (2009)
This study investigated the combined and separate effects of creativity, emotional intelligence, motivation, introversion and extroversion on teaching effectiveness of secondary school teachers in Ibadan. The study was carried out in 10 randomly selected secondary schools in Ibadan North Local Government area of Oyo State. The study population comprised entire teaching staff in the selected schools. Three hundred teachers however, participated in the study. Six validated instruments were used to collect data. The result indicated that the five independent variables contributed significantly both jointly and relatively to the prediction of teaching effectiveness. On the basis of this findings, it is recommended that creativity, emotional intelligence and personality factors should be considered in the course of recruiting people into teaching profession. Furthermore, teachers’ motivation should be considered as of paramount importance